Implikasi Kepemilikan Institusional terhadap Discretionary Accrual - Abdul Haris (Fakultas Ekonomi Universitas Panca Marga, 2015)
Changes in the world economic system that occurred in late as a result of globalization will affect Indonesian economic and legal system. A number of studies have examined the discretionary accrual, and this study also takes this topic. It investigates the impact of highly ownership concentration on discretionary accrual. The researcher is interested in Indonesian companies that their ownership concentrates on a few owners in form of institution with the majority of Limited Corporation. Samples in this study are firms listed in the Jakarta Stock Exchange 2006-2011. Multiple regression analysis is used to test the hypotesis. The dependent variables are discretionary accrual and the independent variables of the ownership proportion by institutions are measured with the first biggest ownership by institutions. The control variables are leverage, size and return. The result of this study suggests that the companies owned by institutions do discretionary accrual in income decreasing to avoid political cost. Keyword: earnings management, institution ownership, and discrenionary accrual.